Virtual infection prevention—The next frontier. (5th November 2021) - Pryor, Rachel J.; Vokes, Rebecca; Anderson, Deverick; Bearman, Gonzalo
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has resulted in the acceleration of telehealth and remote environments as stakeholders and healthcare systems respond to the threat of this disease. How can infectious diseases and healthcare epidemiology expertise be adapted to support safe care for all?